Prevalence And Susceptibility Of Staphylococcus Aureus Nasal Carriage Strains Isolated From Haemodialysis Patients - Khairunnisa Mohd Sukri; Ilina Isahak; Abdul Aziz Marwan; Nurul Azmawati Mohamed @ Abd Aziz (UPM, 2024)
MJMHS VOL.19 NO. 1 Page (181-189)